Tone mapping to minimize visual sensation distortion considering brightness and local band‐limited contrast. Issue 10 (1st December 2017) - Shin, Seungjun; Kong, Kyeongbo; Lee, Junggi; Song, Woo‐Jin; Kwon, Kyung Joon; Kim, Seong Gyun
Abstract: We propose a tone‐mapping algorithm that minimizes the function that represents the visual sensation distortion that occurs after tone mapping. For the function, we consider both brightness and local band‐limited contrast to reduce darkening of images that have high dynamic range when they are displayed with conventional contrast‐based tone mapping using histogram on devices that have low dynamic range. By exploiting human visual characteristics, we simplify the problem and find a closed‐form solution that minimizes the function that represents distortion of visual sensation. In both subjective and objective evaluations, the proposed algorithm achieves a processed image that is most similar to the original image and has the best subjective image quality. Abstract : This paper proposes a tone‐mapping algorithm that minimizes the function that represents the visual sensation distortion that occurs after tone mapping. By exploiting human visual characteristics, we simplify the problem and find a closed‐form solution that minimizes the function that represents distortion of visual sensation. In both subjective and objective evaluations, the proposed algorithm achieves a processed image that is most similar to the original image and has the best subjective image quality.